Does "Halalness" Affect Young Muslims’ Intentions to Use the COVID-19 Vaccine? - Sudarsono, Heri; Ikawati, Retty; Azizah, Siti Nur; Kurnia, Agus; Nuanmark, Ponchanok (Indonesian Journal of Halal Research, 2023)
Young Muslims comprise a large population in Indonesia. This study analyzes the effect of halal awareness, halal certification, attitudes, subjective norms, perceived behavior controls and vaccine quality on young Muslims' intentions to use the COVID-19 vaccine. This study involved 699 random respondents from 32 provinces in Indonesia. This research model develops Theory Planned Behavior (TPB) using structural equation modeling (SEM) with partial least squares structural equation modeling (PLS-SEM) data processing tools. The results showed that halal awareness and certificates had a P-value of <0.05 or positively affected Muslims' attitude towards vaccines. Likewise, halal awareness, attitudes, subjective norms and vaccine quality have a P-value of <0.05 and perceived behavior control has a P-value of <0.10 or positively affects Muslims' intentions to use vaccines. However, halal certification has a P-value of >0.10 or does not affect their intention to use vaccines. Islamic values remain a consideration for young Muslims in using the COVID-19 vaccine. Therefore, the government needs to include halal aspects in determining policies related to the implementation of vaccinations.